2019
DOI: 10.1002/anie.201902815
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Study of Acoustically Levitated Droplets Illuminates Molecular‐Level Mechanism of Photodynamic Therapy for Cancer involving Lipid Oxidation

Abstract: Even though the general mechanism of photodynamic cancer therapy is known, the details and consequences of the reactions between the photosensitizer‐generated singlet oxygen and substrate molecules remain elusive at the molecular level. Using temoporfin as the photosensitizer, here we combine field‐induced droplet ionization mass spectrometry and acoustic levitation techniques to study the “wall‐less” oxidation reactions of 18:1 cardiolipin and 1‐palmitoyl‐2‐oleoyl‐sn‐glycero‐3‐phospho‐(1′‐rac‐glycerol) (POPG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 56 publications
1
50
0
Order By: Relevance
“…To further confirm that the oxygen functionalities of OAOOH − and OAOH − are indeed hydroperoxyl and hydroxyl groups, H/D exchange experiments were performed by using a droplet comprising D 2 O. Both ‐OOH and ‐OH have one exchangeable H atom . The FIDI‐MS spectra in Figure show that both OAOOH − and OAOH − have 1 Da shift, meaning that there is an acidic H in each case.…”
Section: Figurementioning
confidence: 93%
“…To further confirm that the oxygen functionalities of OAOOH − and OAOH − are indeed hydroperoxyl and hydroxyl groups, H/D exchange experiments were performed by using a droplet comprising D 2 O. Both ‐OOH and ‐OH have one exchangeable H atom . The FIDI‐MS spectra in Figure show that both OAOOH − and OAOH − have 1 Da shift, meaning that there is an acidic H in each case.…”
Section: Figurementioning
confidence: 93%
“…In the current study, we adopt our unique home-built field-induced droplet ionization mass spectrometry (FIDI-MS) methodology (Figure 1), which is capable of selective online sampling of molecules that reside at the air-water interface and suffers minimal influence from the bulk of the solution. [27][28][29][30] Amphiphilic lipids, the major oxidation target of PDT, [1] and their oxidation products especially those unstable products that could easily degrade, can be detected by FIDI-MS in an in situ manner. The posterchild PS, 5,10,15,20-tetra(m-hydroxyphenyl)chlorin (temoporfin, T for short), is selected in this study for its high quantum yield and benign, tissue-penetrating activation wavelength (652 nm).…”
mentioning
confidence: 99%
“…[32] In previous studies, only Type II mechanism was unambiguously reported for T, but the possible involvement of a Type I pathway remains elusive. [28,[32][33][34] Details of the experimental methods are provided in the Supporting Information. Briefly, the FIDI-MS setup features a hanging water droplet (ca.…”
mentioning
confidence: 99%
“…Both -OOH and -OH have one exchangeable H atom. [22] The FIDI-MS spectra in Figure 5 show that both OAOOH À and OAOH À have 1 Da shift, meaning that there is an acidic H in each case. Apparently H atoms are more extensively exchanged by D in OAOOH À than in OAOH À , consistent with the fact that -OOH is more acidic than -OH.…”
Section: Angewandte Chemiementioning
confidence: 99%